2015
DOI: 10.1111/acer.12696
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethanol Exposure In Utero on Cajal–Retzius Cells in the Developing Cortex

Abstract: Background Prenatal exposure to ethanol exerts teratogenic effects on the developing brain. Here, we tested the hypothesis that exposure to ethanol in utero alters the disposition of Cajal–Retzius cells that play a key role in orchestrating proliferation, migration, and laminar integration of cortical neurons in the embryonic cortex. Methods Pregnant Ebf2-EGFP mice, harboring EGFP-fluorescent Cajal–Retzius cells, were subjected to a 2% w/w ethanol consumption regimen starting at neural tube closure and lasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…1B, right; Control truex¯=199.7±14.2 moves; EtOH truex¯=258.7±14.4 moves; Unpaired t test, P<0.01). In line with our investigation of open field exploratory activity at adolescent ages (Skorput and Yeh, 2015), this hyperactive phenotype confirms that our chronic maternal ethanol consumption regimen is a viable model for investigating the enduring aberrances in cortical form and function associated with FASD.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…1B, right; Control truex¯=199.7±14.2 moves; EtOH truex¯=258.7±14.4 moves; Unpaired t test, P<0.01). In line with our investigation of open field exploratory activity at adolescent ages (Skorput and Yeh, 2015), this hyperactive phenotype confirms that our chronic maternal ethanol consumption regimen is a viable model for investigating the enduring aberrances in cortical form and function associated with FASD.…”
Section: Resultssupporting
confidence: 85%
“…However, not examined was whether such a chronic prenatal ethanol exposure-induced aberrant pattern of migration might also be associated with enduring cortical abnormalities later in life. Additionally, our more recent work investigating the teratogenic effects of in utero ethanol exposure on Cajal-Retzius cells during corticogenesis (Skorput and Yeh, 2015) further supports a role for aberrant cortical development in the etiology of FASD. In the present study, we build and expand on these initial studies and ask whether chronic low-level ethanol exposure in utero can lead to FASD-relevant behavioral abnormalities and enduring aberrances in cortical form and function into adulthood.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…It was later found that mice receiving the same paradigm exhibited altered patterning of spontaneous GABA-mediated synaptic barrages and increased GABA-mediated synaptic activity, while showing an increase in Cajal-Reizius cell numbers in cortical layer I (Skorput and Yeh 2015). Similar PAE-induced frontal cortex neuron abnormalities have been previously demonstrated in other mouse models implementing a chronic liquid diet for PAE, including the loss of GABAergic neurons in an acute 3rd trimester PAE paradigm (Skorput and Yeh 2015; Smiley et al 2015; Abbott et al 2016), in parallel with the altered neuronal circuitry seen in individuals with FASD (Rema and Ebner 1999; Sowell et al 2008). Importantly, at PN20 PAE, offspring show increased anxiety and impaired gross and fine motor coordination (El Shawa et al 2013).…”
Section: Mouse Models Of Prenatal Alcohol Exposurementioning
confidence: 99%